2017
DOI: 10.3390/en10040568
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of Melting of Encapsulated CaCl2·6H2O for Thermal Energy Storage Technologies

Abstract: Abstract:We present in this work simulations using the finite difference approximation in 2D for the melting of an encapsulated phase-change material suitable for heat storage applications; in particular, we study CaCl 2 ·6H 2 O in a cylindrical encapsulation of internal radius 8 mm. We choose this particular salt hydrate due to its availability and economic feasibility in high thermal mass building walls or storage. Considering only heat conduction, a thermostat is placed far from the capsule, providing heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Copper [29] Steel [30] Aluminum [13] Nickel [29] Density (kg/m Properties-thermoplastic PVC [31] Resin epoxy [23] Polystyrene [32] Polypropylene [33] Density (kg/m The length (LPV), the depth (lb) and the thickness (eb) of the aluminum box were taken as 1m, 30mm and 4mm respectively. The inclination angle of the system, the ambient temperature, the incident radiation and the solar radiation absorption coefficient were all chosen as 45 o , 293K, 750W/m 2 and 0.9 respectively.…”
Section: Properties-metalmentioning
confidence: 99%
“…Copper [29] Steel [30] Aluminum [13] Nickel [29] Density (kg/m Properties-thermoplastic PVC [31] Resin epoxy [23] Polystyrene [32] Polypropylene [33] Density (kg/m The length (LPV), the depth (lb) and the thickness (eb) of the aluminum box were taken as 1m, 30mm and 4mm respectively. The inclination angle of the system, the ambient temperature, the incident radiation and the solar radiation absorption coefficient were all chosen as 45 o , 293K, 750W/m 2 and 0.9 respectively.…”
Section: Properties-metalmentioning
confidence: 99%
“…Moreover, such operations resulted in decreased PCM mass by about 1.5%. Puertas et al [110] used numerical simulations to examine the influence of the capsule's thermal conductivity on the melting time of PCM. They found that the melting time decreased by 20% when the thermal conductivity of the capsule increased 100 times.…”
Section: Encapsulationmentioning
confidence: 99%
“…The phase transition process caused by changes in ambient temperature employs the latent heat method to store and release thermal energy. Constant temperature can be maintained by isothermal absorption and release of heat; this enables efficient use of energy in space and time [8][9][10][11]. PCMs are widely used in a wide range of energy conversion fields such as waste heat recovery, Li-ion batteries, building insulation, and solar energy storage [12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%